"Racial realism II: Are folk races real?". Issue 1 (19th October 2017) - Spencer, Quayshawn
Abstract: This article is Part II in a pair of articles on racial realism. In Part I, I defined "racial realism" and discussed the major attempts in the past twenty years among metaphysicians of race and biologists to defend racial realism from the viewpoint of what biologists mean by "race." In this article, I continue discussing and critiquing how metaphysicians of race have conceived of and defended racial realism, but with a focus on how ordinary people use "race." I focus on two broad groups of racial realisms in this article: biological racial realism and social racial realism. After defining each one, I summarize a representative sample of recent attempts from metaphysicians of race to defend both types of racial realism. I also discuss major criticisms against each attempt. I end by sketching a new, radical pluralist way of being a racial realist, and I provide some empirical motivation for why it's promising.